A New Method for Thiomethylation of Hydroxy-1,4-naphthoquinones with N-Acetyl-l-cysteine; First Synthesis of Fibrostatins B, C, and D - Sabutskii, Yuri E.; Polonik, Sergey G.; Denisenko, Vladimir A.; Dmitrenok, Pavel S. (Synthesis, 2014)
A series of N-acetyl-S-[(3-hydroxy-1,4-dioxo-1,4-dihydronaphthalen-2-yl)methyl]-l-cysteine conjugates were obtained in good yields by acid-catalyzed condensation of substituted 2-hydroxy-1,4-naphthoquinones with N-acetyl-l-cysteine and paraformaldehyde. Based on this reaction, a first synthesis of fibrostatins B, C, and D was developed.
Keywords: quinones; thiols; natural products; fibrostatins; amino acids